Human Helminthiasis - Rodrigo, Luis (IntechOpen, 2017)
Human helminthiasis, known as worm infections, is any macroparasitic disease affecting humans, in which a part of the body is invaded by a lot of worms, known as helminths. They are broadly classified into flukes, tapeworms, and roundworms. Soil-transmitted helminthiasis and schistosomiasis are the most important, being included into the neglected tropical diseases. Helminthiasis has been found to result in poor birth outcome, less cognitive development, lower school and work performance, lower socioeconomic development, and poverty. Soil-transmitted helminthiases are responsible for parasitic infections in as much as a quarter of the human population worldwide. This group of infective diseases has been targeted under the joint action of the world's leading pharmaceutical companies and local governments, trying to achieve their eradication.